Algoritma Sistem Koordinasi Pembangkit Listrik Hibrid PV-Generator 3 Fasa - wahyudi, Agus; Rajagukguk, Antonius; Rosma, Iswadi Hasyim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
The need for electrical energy is increasing along with population growth and increasing community activities, so it is necessary to add new energy sources to reduce fossil resources. One alternative renewable energy issolar energy using photovoltaic (PV). However, so that the load can still be supplied optimally, one alternative solution is to use a hybrid generator technique. Hybrid system is the concept of combining two or more energysources. One of the hybrid power plants that has the potential to be developed is a combination of PV and generator. This research makes a hybrid PV-generator generating system to serve the maximum load and complement each other's shortcomings and add a battery as an additional generator. This research creates a coordination of generators to interact with each other between generators to serve load patterns in a structuredand simulated manner in MATLAB 2016a. The design of the hybrid power plant is PV with 58 kwp power, 30 kAh battery and 25 kva generator. The results in this study show the performance of each generator whenserving the load. Loads of 10 kw, 20 kw and 30 kw are supplied by PV and batteries. At peak load, the load is supplied by a hybrid PV-generator or battery-generator. From the simulation results show that the generator isable to overcome any given load with a given coordination system.Keywords : Photovoltaic (PV), Hybrid, generator, load, Matlab 2016a